Citrus Reset Analysis - Ronald P. Muraro; Fritz M. Roka (EDIS, 2003)
This is EDIS document FE365, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published March 2003.